Design of reinforced shotcrete arches in rock tunneling projects - A literature and case study that aims to illustrate the complexity of designing reinforced steel rebar shotcrete arches - Marklund, Simon (My University, 2022)
Reinforced steel rebar shotcrete arches are a support measure that is commonly used where poor rock conditions prevail, such as thin rock coverage and fault zones. Further, technical challenging projects with for example wide tunnel spans, for example in the West link project, can justify the use of these arch solutions. However, as of right now in Sweden, there are no clear requirements or recommendation on how to properly design these arches. There are also no clear separation between when the arch are interacting with the rock mass and when it can be considered a stand alone steel concrete construction. This causes confusion in the designing phase since it is not clear if a rock mechanical or a structural engineer should be assigned to the problem. It is also not clear which requirement documentation, such as "Projektering av bergkonstruktioner", TRVINFRA-00233 and Eurocode, that are applicable. This thesis aims to illustrate these problems and to provide more documentation and knowledge on the subject. A more clear design process of reinforced steel rebar shotcrete arches would likely simplify the designing phase for the engineers. It would also benefit the developer since it would be easier to control constructed arches against the drawings and tolerances. To solve the mentioned problems this thesis has conducted a literature and case study review on the topic. The literature review gathers information on the decision making and design process of support measures in general but focuses on reinforced steel rebar shotcrete arches specifically. The case study review covers cases in Sweden that have designed and constructed reinforced steel rebar arches. The combined knowledge gained by conducting a extensive literature review, case study review and consulting experts on the subject has shown that the national requirements and recommendation regarding reinforced shotcrete arches are limited. There are also no clear distinction whether the arch interacts with the rock mass, making it hard to consider the arch as a stand alone structure where Eurocode is applicable. It is suggested that the available requirements and recommendation documents in Sweden are further developed regarding reinforced shotcrete arches. It is also suggested that the presence of rock bolts could define if the arches are interacting with the rock mass which would make it clear what design approach that could be used.
Keywords: support measures; requirements; tunneling; reinforced steel rebar shotcrete arches; design process